Don't look and it won't hurt - Peck, Richard, 1934- (New York : Holt, 1999)
A teenage girl struggles to understand her place within her family and in the world.
Young Adult
Keywords: Family problems -- Fiction; Interpersonal relations -- Fiction; Mothers and daughters -- Fiction; Sisters -- Fiction; Family problems -- Fiction; Interpersonal relations -- Fiction; Mother-daughter relationship -- Fiction; Sisters -- Fiction